Anti-Abortion Mobilization in Latin America: Signs of a Field in Transformation - Marta Rodriguez de Assis Machado; María Angélica Peñas-Defago; Camila Gianella Malca (Revista Direito GV)
Abstract Gender and sexuality have become a focal point of the political divide in Latin America. In many countries, religious actors, political leaders, pro-life and pro-family nongovernmental organizations (NGOs), among others, have come together to promote a neoconservative shift in contemporary regional politics. Despite the constant public presence of religious actors and their long-standing influence on public policies in the region, recent challenges to sexual and reproductive rights have come from a field in transformation. The anti-abortion mobilization shows important signs of adaptation and mutation on different fronts – networks, alliances, strategies, and frameworks. Finally, this process of renovation has led to the expansion of this dispute towards a broader anti-gender alliance, and the increasing importance of legal strategies and tools by anti-abortion actors is remarkable. The transformations in the anti-abortion field were globally put into action after the conservatives’ defeat in the UN Conference in Cairo, and they also interacted with different local processes, in response to the relational dynamics between movement and countermovement. However, we can see important convergences among Latin-American cases. Drawing on evidence from case studies of countries in the region, this article analyses the main characteristics of contemporary anti-abortion activism in Latin America. It identifies significant commonalities among the cases and raises the hypotheses that shifts in the composition of the anti-abortion networks, in mobilization strategies and frames are inserted in a trend that has been transnationally diffused and subject to different processes of vernacularization. This article ultimately calls attention to the need for more empirical research to address the regional dynamics of transnational actors, diffusion processes, and local adaptations.